2004
DOI: 10.1038/sj.bjc.6601849
|View full text |Cite
|
Sign up to set email alerts
|

Promoter hypermethylation of the Chfr gene in neoplastic and non-neoplastic gastric epithelia

Abstract: While chromosomal instability is a common feature of human solid tumours, no abnormalities in genes involved in the mitotic checkpoint have been identified. However, recently, Chfr (checkpoint with forkhead associated and ring finger), a mitotic stress checkpoint gene, has been reported to be inactivated due to promoter hypermethylation in several types of human malignancy. To clarify whether Chfr promoter hypermethylation is involved in gastric carcinogenesis, we investigated the promoter methylation status o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 19 publications
2
17
0
1
Order By: Relevance
“…To date, only CHFR, an ubiquitin ligase (Kang et al, 2002), has been shown to be involved in the third mitotic checkpoint (Scolnick and Halazonetis, 2000). CHFR is frequently inactivated in human cancers, mostly owing to the hypermethylation of its promoter region (Mizuno et al, 2002;Honda et al, 2004;Takahashi et al, 2004;Brandes et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only CHFR, an ubiquitin ligase (Kang et al, 2002), has been shown to be involved in the third mitotic checkpoint (Scolnick and Halazonetis, 2000). CHFR is frequently inactivated in human cancers, mostly owing to the hypermethylation of its promoter region (Mizuno et al, 2002;Honda et al, 2004;Takahashi et al, 2004;Brandes et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, several groups have shown that CHFR mRNA expression is lost or decreased in primary tumors and cancer cell lines when compared with matched normal tissues and cells. The best characterized means of expression loss is promoter hypermethylation, which occurs in a subset of tumors and cell lines and the frequency of which seems to be dependent on the tissue of origin (4,5,(12)(13)(14)(15)(16)(17)(18)(19)(20). Further support that CHFR may mediate tumorigenesis is that its chromosomal location, 12q24, is a site for allelic imbalance and chromosome rearrangements in several types of cancer (21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Transduce cell lines with the retrovirus construct and select for stable clones (months [12][13][14][15][16][17].…”
Section: Task 2a: Design a Retroviral Vector That Will Have Controllementioning
confidence: 99%
“…Most notably, several groups have shown that CHFR mRNA expression is lost or decreased in primary tumors and cancer cell lines when compared to matched normal tissues and cells. The best characterized means of expression loss is promoter hypermethylation, which occurs in a subset of tumors and cell lines and the frequency of which appears to be dependent on the tissue of origin (4,5,(12)(13)(14)(15)(16)(17)(18)(19)(20). Further support that CHFR may mediate tumorigenesis is that its chromosomal location, 12q24, is a site for allelic imbalance and chromosome rearrangements in several types of cancer (21)(22)(23)(24)(25) This decrease in expression led to the acquisition of many phenotypes associated with malignant progression.…”
Section: Referencesmentioning
confidence: 99%